Equality of Opportunity and Equality of Outcome - Zdenko Kodelja (Center for Educational Policy Studies Journal)
The report on the findings of extensive empirical research on equality of educational opportunities carried out in the US on a very large sample of public schools by Coleman and his colleagues has had a major impact on education policy and has given rise to a large amount of research and various interpretations. However, as some interpreters have highlighted, even more important than the findings of the survey themselves has been Coleman’s redefinition of equality of opportunity, abandoning the then prevailing conception of equality of educational opportunities as equality of starting points and replacing it with the concept of equality of educational opportunities as equality of educational outcomes. The question is, therefore, whether equality of outcomes really is one of the two types of equality of opportunity. The purpose of the present article is to show that equality of opportunity and equality of outcomes are two different types of equality. If they are different, the interpretation that Coleman has redefined the concept of “equality of educational opportunity” turns out to be incorrect.